Combat Fitness for the Elite Female Martial Artist - Sprague Martina (Wish Publishing, 2006)
This book teaches women how to toughen up and become effective martial artists and defenders of self and others. Although there are a few other martial arts books written specifically for women, these books generally focus on a particular style of martial art and give the reader basic information on that art. This book differs by focusing on how women can gain respect as martial artists in a male-dominated environment